The Importance of Computerized Mortuary Registers: A Study Conducted in Sri Lanka - Ariyarathna, H.T.D.W. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2022)
Monitoring of the trends and patterns seen in judicial autopsies is critical for planning interventions in the health sector. Statistical analyses about judicial post-mortems are not adequately performed to date. Anyhow, if there are computerized mortuary registers, such statistical analysis will be an easy task. This research enables the identification of pertinent demographic data, manner and cause of death, inquest types and police jurisdictions in the postmortem examinations conducted in a tertiary care hospital in Sri Lanka. A retrospective descriptive study was conducted over a 5-year period, from January 2015 to December 2019. The data were analyzed with SPSS software and Microsoft Excel 365. The p value, < .05 was set as significant in the chi-square test. Details of 4760 post-mortems were analyzed in total. The autopsies had a male to female ratio of 3.7:1. The number of postmortems performed varied by month, and no clear pattern was discernible. There was a nearly twofold increase in autopsies performed on people aged 50 and under. There was no significant relationship between the ability to provide the cause of death and sex. Significant associations were observed between age and the ability to provide the cause of death, between the ability to provide the cause of death and the type of inquest, and between the type of inquest and the manner of death. The ratio of magisterial inquests to those conducted by the Inquirer into Sudden Deaths (ISDs) was 1:11.5. The ratio of natural to unnatural to undetermined autopsies was 5:2:1. Mt Lavinia, Dehiwala, and Piliyandala were the three police areas most heavily involved. It is emphasized in this study that combining findings with a Geographic Information System in the context of geospatial technology can widely be used in the field of Forensic medicine too.
Keywords: cause of death, manner of death, inquest type, judicial postmortems, Geographic Information System (GIS), computerized mortuary registers